2010
DOI: 10.1080/17518251003623376
|View full text |Cite
|
Sign up to set email alerts
|

“Green Star”: a holistic Green Chemistry metric for evaluation of teaching laboratory experiments

Abstract: This paper presents a new semi-quantitative metric, Green Star (GS), for evaluation of the global greenness of chemical reactions used in teaching laboratories. Its purpose is to help choose the more acceptable reactions for implementing Green Chemistry (GC) and to identify suitable modifications of protocols to improve the greenness of the chemistry practiced by students. GS considers globally, in principle, all the Twelve Principles of GC. The metric consists in the evaluation of the greenness of the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 9 publications
1
59
0
8
Order By: Relevance
“…Green Chemistry Letters and Reviews 3 coefficients. The greenness was also evaluated considering all the 12 Principles of Green Chemistry by calculation of the Green Star, as reported elsewhere (16,19).…”
Section: To Evaluate Waste Minimizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Green Chemistry Letters and Reviews 3 coefficients. The greenness was also evaluated considering all the 12 Principles of Green Chemistry by calculation of the Green Star, as reported elsewhere (16,19).…”
Section: To Evaluate Waste Minimizationmentioning
confidence: 99%
“…The experimental values of the metrics used in the present discussion were obtained in the studies reported before (16,19). Table 4 presents a road map of the present study, showing for each case the conditions that were changed in successive synthesis experiments and the metrics influenced by them, as described below.…”
Section: Preparation Of Case Studiesmentioning
confidence: 99%
See 3 more Smart Citations